Emotional education in post-pandemic times: emerging needs and educational response - González-Herrera, Ana Isabel; Yanes-Rodríguez, Laura; Reyes-González, Natalia; Alonso-Rodríguez, Isabel; Pérez-Jorge, David (Institute of Advanced Engineering and Science, 2025)
COVID-19 has provoked a rapid adaptation in the post-pandemic period, posing a great challenge for all areas, particularly education. This paper presents an action-research study in a Spanish educational institution, aiming to determine the emotional impact that COVID-19 has left on primary school students, with special attention to students with specific educational needs (SEN). In addition, the aim was to articulate a proposal for improving emotional education addressed at school. As a result of this study, the socio-affective needs of the pupils and the benefits of psychomotricity and artistic education for strengthening emotional development have been discovered. As a result, an innovative project has also been proposed for educational guidance and tutoring at CPEIPS La Salle La Laguna, based on the programming of cross-cutting units in various subjects to optimize the socio-emotional and psychomotor development of the students.